The impact of social media for educational use and educational information sharing towards students’ academic performance - Jamalludin, Nur Hafifah; Wok, Saodah (2018)
Social media has contributed a lot in the academic field. Students are keen to use the social media as a platform for them to grasp academic-oriented information and materials online. As such, in light of the Social Learning Theory (SLT), this study tries to examine the impact of the social media for educational use and educational-information sharing towards students’ academic performance in International Islamic University Malaysia (IIUM). SLT helps to explain the impact on students’ academic performance when the social media is utilised for their study. A quantitative research design is employed, using survey method with questionnaire as an instrument for data collection. A total of 440 undergraduate students from Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS) participated in this study. This study finds that students’ academic performance is significantly correlated with their social media for educational use and their educational-information sharing activities. Educational-information sharing is also found to partially mediate the relationship between social media for educational use and students’ academic performance. Therefore, this study contributes to utilising the social media positively in the academic field, which in turn, improves their academic performance. With this, SLT theory holds true.